Welfare economics and social choice theory - Feldman, Allan 1943- (Springer US, 1980)
This book covers the main topics of welfare economics - general equilib rium models of exchange and production, Pareto optimality, externalities and public goods - and some of the major topic of social choice the ory - compensation criteria, fairness, voting, Arrow's Theorem, and stra tegic behavior. The underlying question is this: "Is a particular economic or voting mechanism good or bad for society?" Welfare economics is mainly about whether the market mechanism is good or bad; social choice is largely about whether voting mechanisms can improve upon the results of the market. The book grew out of my undergraduate welfare economics course at Brown University, and it is intended for the undergraduate student who has some prior familiarity with microeconomics. However the book is also use ful for graduate students and professionals, economists and non-econo mists, who want an overview of welfare and social choice results unbur dened by detail and mathematical complexity